2022
DOI: 10.3390/ijerph19073795
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Children and Adolescents with Neuropsychiatric Disorders: Emotional/Behavioral Symptoms and Parental Stress

Abstract: The objective of our study was to evaluate the impact of the COVID-19 pandemic on the emotional and behavioral symptoms in minors with neuropsychiatric disorders and on parental stress through a standardized neuropsychological assessment, comparing the data collected before the pandemic with those collected during the lock-down. Another goal of our study was to analyze the relationship between parental stress and behavioral/emotional symptoms in children. Our study was conducted on 383 families of patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…Furthermore, in this regard, we should also consider that our study was conducted during the COVID-19 pandemic, and this may have been an additional factor that impacted parental stress [ 30 , 31 , 32 ]. Some recent research showed that the COVID-19 pandemic can be a source of parental stress in parents of children and adolescents with various neuropsychiatric conditions, including epilepsy [ 33 , 34 ]. On the other hand, an observational study by Armeno and colleagues (2022) [ 35 ] did not highlight additional difficulties in managing the KD during the COVID-19 pandemic and supported the feasibility and safety of initiating and managing the KD by telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this regard, we should also consider that our study was conducted during the COVID-19 pandemic, and this may have been an additional factor that impacted parental stress [ 30 , 31 , 32 ]. Some recent research showed that the COVID-19 pandemic can be a source of parental stress in parents of children and adolescents with various neuropsychiatric conditions, including epilepsy [ 33 , 34 ]. On the other hand, an observational study by Armeno and colleagues (2022) [ 35 ] did not highlight additional difficulties in managing the KD during the COVID-19 pandemic and supported the feasibility and safety of initiating and managing the KD by telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no other previous studies that specifically evaluated stress changes in parents of epileptic children taking PER, but in previous research we found that high level of parental stress was found in parents of children with epilepsy, even in the mildest forms ( 37 39 ). In our work, we did not find significant changes in stress levels perceived by parents after the addition of PER.…”
Section: Discussionmentioning
confidence: 77%
“…The most relevant aspect of our research concerns psychological problems that, as described by other authors, compromise the daily activities in school-age children ( 19 ). The standardised scales we used for the assessment ( 27 29 , 31 – 35 ) revealed that a large percentage of children aged 8–16 years developed symptoms of social and separation anxiety (37%), panic (32%), tension (30%), obsessive-compulsive tendencies (23%), and generalised anxiety (28%) related to the presence of neurological symptoms ( Table 4 ). Although small in number, some children had depression and PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The Trauma Symptom Checklist for Children-A (TSCC-A) ( 29 ) is a self-assessment questionnaire for children aged 8–16 years, consisting of 44 items and five clinical scales (Anxiety, Depression, Anger, Post-traumatic Stress, and Dissociation). Standardised scores > 65 are considered significant; scores <65 are not significant.…”
Section: Methodsmentioning
confidence: 99%